Pengaruh Politik Hukum Dalam Pembentukan dan Penegakan Hukum di Indonesia - I, Ismaidar; Sembiring, Tamaulina Br.; Saragih, Elisabeth (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Legal politics is a strategic instrument in the formulation and enforcement of laws that reflects the vision, mission, and goals of a state. This article examines how legal politics influences the drafting of legislation and its implementation in law enforcement in Indonesia. Using a descriptive qualitative approach, this study reveals that legal politics in Indonesia is shaped by various political, economic, social, and cultural dynamics. The findings highlight challenges in maintaining the integrity and independence of the legislative process and law enforcement due to political interference. This article recommends strengthening oversight mechanisms and increasing public participation in legal politics to establish a more just and accountable legal system.